Research on the Deficits and Resolutions of China’s Food Recall System: Based on a Comparative Legal Perspective - Chang, Huan (International Journal of Social Sciences and Public Administration, 2026)
The Food Safety Law of the People’s Republic of China (2025 revision) largely maintains the food recall provisions originally established in its 2015 revision. While these revisions represent a refinement of the food recall system, an examination of its past implementation suggests that inherent design flaws and insufficient supporting measures appear unresolved by this amendment, potentially undermining its practical effectiveness. Persistent deficiencies primarily include outdated and ambiguous food safety standards, the impracticality of relying solely on food enterprises as key stakeholders to fulfill recall obligations, and inadequate transparency in the disclosure of regulatory information. Using the comparative legal method, the author draws on the beneficial experiences of the United States’ multi-agency collaborative supervision model and Australia-New Zealand’s single-agency-led model to propose targeted recommendations: promoting the updating and international alignment of food safety standards, reinforcing governmental regulatory responsibility, increasing the cost of violations while establishing incentive mechanisms to encourage proactive recalls by enterprises, and enhancing platforms for food traceability and recall information. The ultimate objective is to safeguard the safety of every bite of food.